Evaluative language: a contrastive analysis of engagement resources used in English and Vietnamese research articles - Hong, Nguyen Bich (Penerbit Universiti Kebangsaan Malaysia, 2025)
Evaluation can be said to be one of the most fundamental functions of language that merits in-depth research. Therefore, evaluative language has recently attracted a lot of attention from linguists worldwide. However, the term seems rather new in the Vietnamese linguistic community. In order to shed further light on the use of evaluative language in Vietnamese in comparison with that in another language, a contrastive analysis of the use of engagement resources in the Appraisal framework by Martin and White (2005) in a corpus of 72 empirical research articles (36 in Vietnamese and 36 in English) was carried out. Results show that English and Vietnamese writers share a lot of similarities in their ways of thinking and expressing their engagement in research articles. They tend to contract the dialogistic space more than expand it. They make use of the engagement resources the most in the Discussion/ Conclusions section and hardly use engagement in the Methods section. However, English writers express engagement more frequently than their Vietnamese counterparts. The results of the study are hoped to be of reference for article writers as well as to enrich literature materials for the fields of evaluative language and academic writing pedagogy in Vietnam.